Increasing The Efficiency of Cargo Delivery to Consumers (Eurasian Journal of Engineering and Technology, 2022)
At present, in a market economy, it is important to ensure the prompt delivery of goods to consumers. To fully meet the needs of consumers and manage the volume of goods, it is also important to rationalize the values of indicators that affect the efficiency of the transport enterprise. The article presents ways to reduce unproductive waiting time for loading and unloading vehicles and vehicles and loading vehicles by increasing the productivity of the loading and unloading points of the consignor and consumers.